Penerapan Model Pembelajaran Snowball Throwing Berbantu Media Gambar Untuk Meningkatkan Aktivitas Dan Hasil Belajar Materi Pesawat Sederhana Pada Siswa Kelas V SD 8 Gondosari - Suyanto Suyanto (Universitas Muria Kudus, 2018)
In the initial learning conditions of 5th grade students of SD 8 Gondosari simple plane material obtained a result that is student learning activities only by 32% and learning completeness by 27%. So taken a study to overcome this. The study was carried out by applying the media-assisted Snowball Throwing learning model. Because this model is believed to be able to tickle student motivation so that learning outcomes also increase. In carrying out the research conducted in two cycles, conclusions can be drawn, namely through the application of the Snowball throwing model to assist the image media can increase student motivation by 87%, and the completeness of learning outcomes to be 89% with a mean value of 80.